Ischaemic stroke as the initial presentation of a pheochromocytoma associated with neurofibromatosis type 1 - S. W. Gnanathayalan; B. M. S. Fernando; U. Bulugahapitiya (Sri Lanka College of Internal Medicine, 2024)
Pheochromocytoma is a rare but well-recognised manifestation of neurofibromatosis type 1 (NF1). Ischaemic stroke has been rarely reported in patients with pheochromocytoma. It can be due to either hypertension or vasospasm. A 33-year-old woman presented with ischaemic stroke and was evaluated for young stroke. Examination revealed clinical diagnosis of NF 1. She had persistent regular tachycardia and mild hypertension. But she denied features suggestive of pheochromocytoma spells. 24-hour urinary metanephrine level was elevated and there was large left adrenal mass lesion. She underwent left sided adrenalectomy. Histology further confirmed the diagnosis of pheochromocytoma. There should be a lower threshold to suspect pheochromocytoma in patients with NF 1.